Exploring the Impact of On-street Parking in Chittagong City, Bangladesh - Haider, Mohammad Ali; Islam, Md. Taufiqul; Hasan, Syed Mahadi (International Journal of Building, Urban, Interior and Landscape Technology, 2021)
Urban mobility and on-street parking management is a vital challenge in the big cities of developing countries like Chittagong City of Bangladesh. This research explored the on-street vehicle parking situation and its impact on the city dwellers in Chittagong City. Primary and secondary data were processed through descriptive and analytical statistics. The study found that there were very few parking facilities and unplanned urban management for the parking spaces are the main reasons for on-street parking. As an effect, severe traffic congestion, the road gets narrower and the footpath crisis is very common and the drivers are unsatisfied when they drive their vehicles. Passengers are suffering from public transport scarcity transport and women, who cannot avail of overcrowding vehicles and try to avoid it to save from physical harassment. Street neighborhood residents are also the victim of noise pollution, air pollution, accident, and blocked off their business as well as overcrowded people. The tendencies of a rule violation, lack of proper administrative monitoring are the vital reasons behind it. Hence, further investigation and a structural policy are needed to formulate by the city authorities to overcome this situation.